PENGINTEGRASIAN CHARACTER BUILDING PADA MATA KULIAH PRONUNCIATION MELALUI PROJECT-BASED LEARNING - Jamilah, Jamilah (Jurnal Pendidikan Karakter, 2016)
Abstrak: Penelitian ini bertujuan untuk memperbaiki proses pembelajaran mata kuliah Pronunciation dan untuk mengintegrasikan character building ke dalam mata kuliah tersebut. Project-based learning adalah model pembelajaran yang dipilih untuk mencapai kedua tujuan tersebut, dan proyek yang diambil adalah pertunjukan drama. Perbaikan pembelajaran dilakukan dengan model lesson study yang diterapkan pada kelas Pronunciation IB yang terdiri dari 20 mahasiswa. Kegiatan ini dilakukan melalui tiga tahap, yaitu tahap persiapan (plan), tahap pelaksanaan (do) dan tahap evaluasi (see). Data dikumpulkan melalui observasi, dokumentasi, diskusi, dan self assessment. Hasil penelitian menunjukkan bahwa project-based learning adalah model pembelajaran yang tepat untuk mengintegrasikan character building ke dalam mata kuliah Pronunciation. Dengan project-based learning mahasiswa dapat belajar dengan gembira, mampu menerapkan kemampuan pronunciation dalam karya nyata, yaitu bermain drama. Mahasiswa juga memahami orang lain dan bertenggang rasa, bekerja sama dalam tim, bertanggung jawab, menghargai karya orang lain, mengembangkan rasa percaya diri, bersikap kritis, dan terbuka terhadap saran dan pendapat orang lain. Kata Kunci: character building, pronounciation, project based learning INTEGRATING CHARACTER BUILDING IN PRONUNCIATION COURSE THROUGH PROJECT-BASED LEARNING Abstract: This study is aimed at improving the learning process Pronunciation course and integrating character building into the course. Project-based learning is a learning model chosen to achieve these objectives, and the project taken is drama performance. The learning improvement was achieved through lesson study carried out with a model applied to the IB Pronunciation class consisting of 20 students. These activities are carried out through three stages, namely the preparatory stage (plan), the implementation phase (do) and the evaluation phase (see). Data were collected through observation, documentation, discussions, and self-assessment. The results showed that the project-based learning was a learning model appropriate for integrating character building into the Pronunciation course. By the use of project-based learning, the students could learn joyfully and be able to apply the pronunciation ability in the real work, in a drama performance. The students also understood others, developed tolerance, worked together in teams, develiped responsibility, respected the work of others, developed self-confidence, was critical as well as open to suggestions and opinions of others. Keywords: character building, pronunciation, project based learning